7+3(x-2)=10-3(x-3)

Simple and best practice solution for 7+3(x-2)=10-3(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+3(x-2)=10-3(x-3) equation:


Simplifying
7 + 3(x + -2) = 10 + -3(x + -3)

Reorder the terms:
7 + 3(-2 + x) = 10 + -3(x + -3)
7 + (-2 * 3 + x * 3) = 10 + -3(x + -3)
7 + (-6 + 3x) = 10 + -3(x + -3)

Combine like terms: 7 + -6 = 1
1 + 3x = 10 + -3(x + -3)

Reorder the terms:
1 + 3x = 10 + -3(-3 + x)
1 + 3x = 10 + (-3 * -3 + x * -3)
1 + 3x = 10 + (9 + -3x)

Combine like terms: 10 + 9 = 19
1 + 3x = 19 + -3x

Solving
1 + 3x = 19 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
1 + 3x + 3x = 19 + -3x + 3x

Combine like terms: 3x + 3x = 6x
1 + 6x = 19 + -3x + 3x

Combine like terms: -3x + 3x = 0
1 + 6x = 19 + 0
1 + 6x = 19

Add '-1' to each side of the equation.
1 + -1 + 6x = 19 + -1

Combine like terms: 1 + -1 = 0
0 + 6x = 19 + -1
6x = 19 + -1

Combine like terms: 19 + -1 = 18
6x = 18

Divide each side by '6'.
x = 3

Simplifying
x = 3

See similar equations:

| 4h=20.4 | | 35+90+62+x=180 | | 90*1=100+70*1 | | 6x+18=2(2+x) | | -41=8x-9 | | 10x^2-20x-24=-4 | | 2y^6+5y^5-25y^4=0 | | 4=m(2)+3 | | 32=2n-3n-5n | | 2(3x+40)= | | 7-0.3=12 | | 6x+7+x-x=61 | | 4x^2+18x=20 | | 0.40y-8=4 | | 10=3u-u | | 4(5y+4)=5 | | 0.8(7x+5)=1.1-(x-3) | | 6u^4+39u^3+18u^2=0 | | -1x-5=1 | | s=2s+3.13 | | .50d+10=3 | | 2x+y=1.89 | | 2(x+1)+2=4x-4 | | X-0.21=488.22 | | 4n+3=-15 | | 3(8n)=3 | | 5ax^2+3ax-2ax^2-8ax+4= | | 4(10y-5)=100 | | t=2t+3.13 | | -7x^3*(-b^5)= | | 2x+6-4=76 | | X-(-13)=40-2x |

Equations solver categories